2022
DOI: 10.1111/ene.15321
|View full text |Cite
|
Sign up to set email alerts
|

Integrated evaluation of a panel of neurochemical biomarkers to optimize diagnosis and prognosis in amyotrophic lateral sclerosis

Abstract: Background and purpose This study was undertaken to determine the diagnostic and prognostic value of a panel of serum biomarkers and to correlate their concentrations with several clinical parameters in a large cohort of patients with amyotrophic lateral sclerosis (ALS). Methods One hundred forty‐three consecutive patients with ALS and a control cohort consisting of 70 patients with other neurodegenerative disorders (DEG), 70 patients with ALS mimic disorders (ALSmd), and 45 healthy controls (HC) were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
30
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 76 publications
(86 reference statements)
10
30
3
Order By: Relevance
“…Recently, it has also been shown that biomarkers may be able to differentiate different patient phenotypes. Glial fibrillary acidic protein (GFAP), a marker of astrogliosis, was shown to be higher in ALS patients with cognitive and/or behavioural impairment compared to those without, with the highest levels present in patients with confirmed ALS‐FTD 105 . Further investigations into this preliminary observation are needed.…”
Section: Utilisation Of Blood Biomarkers In Alsmentioning
confidence: 99%
“…Recently, it has also been shown that biomarkers may be able to differentiate different patient phenotypes. Glial fibrillary acidic protein (GFAP), a marker of astrogliosis, was shown to be higher in ALS patients with cognitive and/or behavioural impairment compared to those without, with the highest levels present in patients with confirmed ALS‐FTD 105 . Further investigations into this preliminary observation are needed.…”
Section: Utilisation Of Blood Biomarkers In Alsmentioning
confidence: 99%
“…NFL is an established marker of axonal injury [41]. Although axonal degeneration is not a specific feature of ALS, NFL is considered its most characteristic biomarker since its concentration is higher than in any other neurological disease [42,43]. This may be because neurofilaments are abundantly expressed in the large myelinated axons involved in the degenerative process, which is particularly fast and severe in ALS compared to other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…We wish to thank Drs Aamir, Shah and Mansure for their valuable comments on our recently published report investigating an "integrated panel of neurochemical biomarkers to optimize diagnosis and prognosis in amyotrophic lateral sclerosis" (ALS) [1], and are glad to see that our article stimulates further discussion on the topic of novel biomarkers for motor neuron diseases. The authors correctly point out that screening for urinary biomarkers such as p75ECD may add value in predicting ALS prognosis, while other serum biomarkers, including anti beta-actin (ACTB) and anti proteasome subunit alpha 7 (PSMA7), may be adopted to optimize diagnosis.…”
Section: Reply To the Letter To The Editor In Response To "Integrated...mentioning
confidence: 99%